Feasibility of Developing Traditional Facility-Specific Nursing Home Antibiograms. (October 2020) - Taylor, Lindsay; Howe, Michael; Osman, Fauzia; Crnich, Christopher
Abstract : Background: An antibiogram is a tool for tracking and reporting antimicrobial resistance; the CDC has endorsed as part of a comprehensive antimicrobial stewardship program in nursing homes. We have previously shown that antibiogram utilization has increased in nursing homes, but most facilities employ tools that are not based on facility-specific data. In this study, we investigate the feasibility to develop antibiograms using facility-specific data and compare these results with antibiograms developed using data from multiple facilities that share the same lab and geographic region. Methods: Raw, de-identified culture results from January 1 through December 31st, 2018 were collected from participating nursing homes and their consulting microbiology laboratories under an IRB-exempt protocol. Culture results were entered and stored in REDCap. Number of isolates per species was examined based on nursing home, nursing home laboratory network, and region. Percentage sensitivities of the most frequently isolated species to commonly used antibiotics were calculated at the nursing home and regional level and compared. T tests of the absolute difference between nursing home- and regional level percentage sensitivities were performed. All data analyses were performed in R software. Results: The mean annual cultures per nursing home was 23.5 (SE, ±3.29). Grouping cultures by lab and region increased the mean culture count 6-fold and 12-fold, respectively. The most commonly isolated species were Escherichia coli (29.7%), Enterococcus spp (11.6%), Proteus spp (10%), Klebsiella spp (8.5%). None of the nursing homes had >30 isolates of a single species (Fig. 1). Escherichia coli was the only species that exceeded the 30-isolate threshold when aggregated at the laboratory network level (Fig. 2). Grouping nursing home cultures by region provided the greatest average isolate count across the most common species. The greatest differences in percentage sensitivity between nursing homes and their region were noted for Escherichia coli and Proteus spp to fluoroquinolones (>20% difference; P < .01). The difference in sensitivity was <5% for Escherichia coli to nitrofurantoin. Conclusions: Nursing homes do not generate enough annual isolates to create antibiograms compliant with Clinical Laboratory Standard Institute guidelines. Grouping isolates from multiple nursing homes at the regional level does reliably exceed the 30-isolate threshold for multiple bacterial species but leads to susceptibility estimates that may vary substantially from those observed at the facility level. Alternative tools for tracking antibiotic resistance and guiding antibiotic prescribing decisions at the local level are needed. Funding: None Disclosures: None